2008
DOI: 10.1002/pat.1178
|View full text |Cite
|
Sign up to set email alerts
|

Curing kinetics of the epoxy system diglycidyl ether of bisphenol A/isophoronediamine by Fourier transform infrared spectroscopy

Abstract: The curing reaction of an epoxy system consisting of a diglycidyl ether of bisphenol A (BADGE, n ¼ 0) and isophoronediamine (IPD), was studied by Fourier transform infrared spectroscopy (FTIR). The degree of conversions and the reaction rates at different isothermal curing temperatures were calculated from the infrared spectra using a method derived from Beer's law. This method is based on the ratio of the height of the characteristic absorbance peak to reference absorbance peak. A kinetic model proposed by So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 15 publications
1
18
0
2
Order By: Relevance
“…During epoxy cast curing, epoxide ring opening process is usually accompanied by the occurrence of an increasing peak of the -OH stretching, at 3500 cm -1 . In case of the 50% WS sample, a higher intensity of the absorbance peak (at 3500 cm -1 ) may be observed than for unmodified epoxy resin [26,27]. This fact may be attributed both to the presence of the organic filler in the composite material, as well as the effect catalytic reaction of the curing process caused by the presence of additional -OH groups originating from the filler [28,29].…”
Section: Evaluation Of Composite Materials' Properties and Structurementioning
confidence: 91%
“…During epoxy cast curing, epoxide ring opening process is usually accompanied by the occurrence of an increasing peak of the -OH stretching, at 3500 cm -1 . In case of the 50% WS sample, a higher intensity of the absorbance peak (at 3500 cm -1 ) may be observed than for unmodified epoxy resin [26,27]. This fact may be attributed both to the presence of the organic filler in the composite material, as well as the effect catalytic reaction of the curing process caused by the presence of additional -OH groups originating from the filler [28,29].…”
Section: Evaluation Of Composite Materials' Properties and Structurementioning
confidence: 91%
“…The bands located at 1032 cm -1 corresponded to a C-O-C linkage because of the unreacted epoxide group. Fraga et al (2008) reported that the bands at 1507 and 820 cm -1 could be assigned to the p-phenylene groups in the unreacted epoxide group. The disappearance of bands, as observed in the neat epoxy (ENC0), indicated that all of the epoxide groups reacted during curing and were well blended with the isophorone diamine curing agent (Nunez et al 1995;Fraga et al 2008).…”
Section: Fourier Transform Infrared Spectroscopy Of Nanocellulose (Ncmentioning
confidence: 99%
“…It is known that curing can be monitored by the FTIR technique [34,36]. In this study, the degree of curing of the f-CNT/epoxy nanocomposite was calculated.…”
Section: Degree Of Curing By Ftirmentioning
confidence: 99%
“…However, the feature at 913 cm −1 exhibits no interference [33,37]. The intensity of the band at 913 cm −1 decreases with increasing degree of curing, which means that the band at 913 cm −1 can sensitively reflect the change of the epoxy groups and better obeys the Beer-Lambert law [32,36]. According to the Beer-Lambert law, the absorption peak at 1616 cm −1 of a benzene ring can be regarded as the internal standard, so the degree of curing can be determined from…”
Section: Degree Of Curing By Ftirmentioning
confidence: 99%